Performance analysis of a power generation system for pressure energy recovery at natural gas city gate stations. (August 2022) - Xu, Wenpan; Zhao, Pan; Gou, Feifei; Liu, Aijie; Wu, Wenze; Wang, Jiangfeng
Highlights: An effective power generation system for city gate stations is proposed. The operation boundary of system coupling with CO2 cycle is studied. System equivalent power generation is proposed to evaluate system performance. The performance analysis under design and off-design conditions is executed. Abstract: Worldwide consensus of energy conservation and emissions reduction calls for effective and eco-friendly energy recovery infrastructures in natural gas pipe networks. However, a considerable amount of energy is abandoned by employing pressure regulators in existing city gate stations. In order to recover the exergy and get rid of fossil fuels in the natural gas pressure reduction process, a power generation system for pressure energy recovery at natural gas city gate stations is proposed. Turboexpander is employed to convert the pressure energy into mechanical work, and a carbon dioxide (CO2 ) cycle is combined to recycle the cold exergy in expanded natural gas. Based on the performance investigation of CO2 cycle, the operation boundary of system with variations of inlet parameters is studied. Furthermore, the system design and off-design performance analysis are also carried out. Results show that system energy efficiency and exergy efficiency reach 42.54% and 88.77% respectively, while the energy recovery rate is 88.11% under design conditions. Under off-design conditions, the system exergy efficiency has a parabolic trend with the optimum value 87.1% under 95% mass flow rate. The increased inlet pressure results in raised exergy efficiency and energy recovery rate, but the curves flatten out when the inlet pressure reaches 105% design value.